Facile synthesis of tungsten carbide nanorods and its application as counter electrode in dye sensitized solar cells - Vijayakumar, P.; Senthil Pandian, M.; Lim, S.P.; Pandikumar, A.; Huang, N.M.; Mukhopadhyay, S.; Ramasamy, P. (Elsevier, 2015)
Tungsten carbide nanorods (WC-NRs) are synthesized by pseudomorphic transformation of chemically synthesized W3O8 nanorods using a high-temperature method. The WC-NRs was introduced into dye sensitized solar cell (DSSC) as counter electrode (CE) catalyst to replace the expensive platinum (Pt). The synthesized WC-NRs were characterized by field emission scanning electron microscopy (FESEM), BET surface area analysis and powder X-ray diffraction (PXRD) measurements. The electrochemical properties of WC-NRs counter electrode were studied using electrochemical impedance spectroscopy (EIS) techniques. The photovoltaic performance of the DSSC with WC-NRs counter electrode was evaluated under simulated standard global AM 1.5G sunlight (100 mW/cm2). The solar to electrical energy conversion efficiency (η) of the WC-NRs with binder and binder free based DSSC was found to be 1.92% and 0.59% respectively. The cell performance can be attributed to the WC-NRs network, catalytic redox activity and 1-D efficient charge-transfer network. Such WC-NRs configuration as CE provides a potential feasibility for counter electrodes in DSSC applications.